2013
DOI: 10.3109/08923973.2013.790413
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of the probiotic mixture Ultrabiotique on maintaining the integrity of intestinal mucosal barrier in DSS-induced experimental colitis

Abstract: The etiology of inflammatory bowel diseases which include ulcerative colitis (UC) and Crohn disease has not yet been clarified. Several hypotheses suggest a change in composition of gut microflora along with an impaired mucosal barrier that lead to excessive mucosal immunologic responses. Increased production of nitric oxide (NO) contributes greatly to the tissue injury caused by chronic inflammation. Evidence indicates that the mucus layer covering the epithelium is altered during UC and experimental colitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 39 publications
1
45
0
1
Order By: Relevance
“…The DSS+Prb group received 3% (w/v) of DSS for 5 days and 10 9 CFU/ml of probiotic for 7 days starting from day 3 to the end of the experimental period. The Prb group received 10 9 CFU/ml of probiotic for 7 days starting from day 3. The mice were fed with 200 ul, of daily-prepared suspension of the probiotic formula in skimmed milk by oral gavage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSS+Prb group received 3% (w/v) of DSS for 5 days and 10 9 CFU/ml of probiotic for 7 days starting from day 3 to the end of the experimental period. The Prb group received 10 9 CFU/ml of probiotic for 7 days starting from day 3. The mice were fed with 200 ul, of daily-prepared suspension of the probiotic formula in skimmed milk by oral gavage.…”
Section: Methodsmentioning
confidence: 99%
“…They are described as "live microorganisms which, when ingested in sufficient numbers, convey health benefits to the host" (14). Current data, obtained mainly from animal models of colitis studies, suggest that probiotics such as Bifidobacterium and Lactobacillus improve barrier function and preserve the intestinal epithelial barrier (10,15).…”
mentioning
confidence: 99%
“…LAB such as L. rhamnosus and probiotic mixture composed of L. acidophilus, B. lactis, L. plantarum, and B. breve have shown protection against DSS-induced colitis [40, 41]. IL-10 was not elevated in our experiments, but several studies have reported that Lactobacillus , Bifidobacterium and Streptococcus species induce the production of anti-inflammatory IL-10, although with different effectiveness [4244].…”
Section: Discussionmentioning
confidence: 62%
“…Imbalances in Al, Fe, Cu and Zn levels caused by Al overload can lead to obvious oxidative stress in liver, which further results in damage to hepatic cells and liver dysfunction [36]. Probiotic can alleviate Al toxicity via many mechanisms such as reducing oxidative stress, inhibiting NO synthase-2 expression and so on [37, 38]. When NO is produced in excess, it causes deleterious effect indirectly through the creation of reactive nitric oxygen species (RNOS), responsible for the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%